The effect of inductive teaching strategy on developing self-organized learning and academic achievement for students of basic education in science - Hussain, Payman (Humanities Journal of University of Zakho, 2020)
The aim of the current research is to develop self-organized learning and academic achievement among students of basic education in the science subject using inductive induction teaching strategies. The research sample consisted of (20) basic education students in the science subject, whose ages ranged between (14-15) years, with an average My age is (14.57) and a standard deviation of (0.40). The sample was divided into two experimental and control groups, each of which consisted of (10) students. The study tools consisted of a self-organized learning scale and inductive teaching strategy (prepared by: the researcher), and the results resulted in The effectiveness of the inductive teaching strategy in developing self-organized learning and academic achievement among students of basic education in science in the experimental group.